Efektivitas Pembelajaran Berbasis Studi Kasus Untuk Membentuk Persepsi Mahasiswa Akuntansi Terhadap Corporate Social Responsibility (CSR) â€œStudi Kasus Di PTS X Surabayaâ€ - Yenny Sugiarti; Ni Luh Putu Tresna Santhi (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Education about CSR will shape students' understanding and perceptions of CSR, so that higher education, especially accounting majors must determine appropriate learning methods so that students understand and have positive perceptions about CSR. The purpose of this research is to determine the effectiveness of the case-based learning method to form positive perceptions about CSR for accounting students when online learning is carried out during the COVID-19 pandemic. This research was conducted at the accounting department of PTS X, a private university in Surabaya.This study used a mixed method between qualitative analysis which was obtained the data through interviews, document analysis and observation and was strengthened by the results of descriptive statistics whose data were obtained through distributing questionnaires to 67 students. The results of this study indicate that the case study-based learning method is still effective in forming positive perceptions of accounting students about CSR even though learning is carried out online during pandemic. Accounting students have a good understanding of the responsibilities that must be carried out by companies, not only economic responsibilities but also legal responsibility, ethical responsibility, stewardship principle, company employee-relationship, and social responsibility. The results of this study also show that students perceive that CSR is beneficial for companies. This research was conducted with one shot study, so it does not measure the difference between before and after study CSR. Future research is expected to be carried out using a longitudinal model or a cross-sectional model so that can measure the differences in perceptions between before and after study CSR.